Implementation of The Project Based Learning Model to Improve the Creativity of Grade V Students at SDN 1 Weru Lor - Oktaviani, Anggra; Fikriyah, Fikriyah; Iman, Bagus Nurul (Journal of Educational Sciences, 2025)
This research was motivated by the need for educational innovation under the Merdeka Curriculum to boost 21st-century skills, especially creativity, in Indonesian human resources. Initial observations at UPTD SD Negeri 1 Weru Lor showed that a conventional 5th grade IPAS (Science and Social Studies) teaching method resulted in only 15% of students demonstrating creativity, demanding a change in approach. The study aimed to implement, assess the results of, and analyze the effectiveness of the Project-Based Learning (PjBL) model in improving the creativity of 5 th grade students. The methodology used was Kemmis and McTaggart’s Classroom Action Research (CAR), conducted over two cycles, involving planning, action, observation, and reflection. Data was collected via teacher and student activity observations, learning outcome tests, and documentation. The results showed a significant improvement. In Cycle I, average student creativity was 55.58% (Moderately Creative), with only 20.68% learning mastery. Following improvements in Cycle II, student creativity soared to 95.79% (Very Creative), and learning outcome mastery reached 96.55%. Teacher performance also increased from 95.23% to100%. The study concludes that the application of the PjBL model is significantly effective in increasing both creativity and learning outcomes for 5th grade IPAS students at UPTD SD Negeri 1 Weru Lor.